Psychological preparation and coping strategies: reflections from Paralympians - Kirk, T. N.; McKay, C.; Foy, J. (International Journal of Sport and Exercise Psychology, 2023)
The purpose of this inquiry was to explore and describe the experiences of Paralympic athletes regarding psychological preparation and coping strategies in elite sport. Seven Paralympic athletes composed written reflections regarding their experiences using psychological skills training. Data analysis yielded three interrelated themes: (a) "we use many different tools": the varied uses of psychological skill training, (b) "mindset is very important - dare I say just as important as skill": mindset matters, and (c) "I hate to lose, but I also know how to move forward": learning through losing. Findings indicated that participants considered psychological skills to be an important part of their approach to sports competition.